Lq-perturbations of leading coefficients of elliptic operators: Asymptotics of eigenvalues - Vladimir Kozlov (Abstract and Applied Analysis)
We consider eigenvalues of elliptic boundary value problems, written in variational form, when the leading coefficients are perturbed by terms which are small in some integral sense. We obtain asymptotic formulae. The main specific of these formulae is that the leading term is different from that in the corresponding formulae when the perturbation is small in L∞-norm.